PENGARUH GAYA MENGAJAR DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR BACKHAND GROUNDSTROKES TENNIS âSTUDI EKSPERIMEN DI FAKULTAS ILMU KEOLAHRAGAANUNIVERSITAS NEGERI MEDANâ - Siregar, Fajar Sidik (STOK BINA GUNA MEDAN, 2017)
This study aims to determine the Effects The Style of teaching and motivation to learning the results of backhand groundstrokes in the game of Tennis. In addition, research also aims to determine the effect of motivation on both the teaching style. Teaching style in this study is the reciprocal of teaching styles and practice style teaching style, and motivation to learn the motivation to learn high and low learning motivation.Research conducted at the Educational health body and rekreasion FIK Unimed 2012/2013 academic year (Semester 2). The research method is an experiment with a 2x2 ftreatment by level design with sample size of 52 people. The results of this study are as follows: (1) overall there is a difference between teaching styles Inklusi and teaching styles Check Self of backhand groundstrokes learning outcomes, (2) for students who have high motivation to learn, giving Inklusi teaching style to give a better effect than Check Self teaching style on learning outcomes backhand groundstrokes, (3) for students who have low learning motivation,the provision of Check Self teaching style to give a better effect than the Inklusi of teaching styles to learning the backhand groundstrokes, and (4) there is interaction between the teaching style with motivation towards learning outcomes backhand groundstrokes.